2016
DOI: 10.5194/acp-16-6577-2016
|View full text |Cite
|
Sign up to set email alerts
|

Size-resolved morphological properties of the high Arctic summer aerosol during ASCOS-2008

Abstract: Abstract. The representation of aerosol properties and processes in climate models is fraught with large uncertainties. Especially at high northern latitudes a strong underprediction of aerosol concentrations and nucleation events is observed and can only be constrained by in situ observations based on the analysis of individual aerosol particles. To further reduce the uncertainties surrounding aerosol properties and their potential role as cloud condensation nuclei this study provides observational data resol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 98 publications
2
19
0
Order By: Relevance
“…This observation can be most plausibly explained by the pinning effect caused by the fast evaporation of the solvent from a droplet deposited on a substrate (Deegan et al, 1997). Similar halo formation has been described for other atmospheric particles (Hamacher-Barth et al, 2016) but we believe that this effect does not have a significant im- Figure 8. DMA-NH 3 co-uptake at DMA / NH 3 gas molar ratios of 0.5 (Table 1) pact on the general uptake observations here.…”
Section: Uptake Into Oxalic Acid Particlessupporting
confidence: 67%
See 1 more Smart Citation
“…This observation can be most plausibly explained by the pinning effect caused by the fast evaporation of the solvent from a droplet deposited on a substrate (Deegan et al, 1997). Similar halo formation has been described for other atmospheric particles (Hamacher-Barth et al, 2016) but we believe that this effect does not have a significant im- Figure 8. DMA-NH 3 co-uptake at DMA / NH 3 gas molar ratios of 0.5 (Table 1) pact on the general uptake observations here.…”
Section: Uptake Into Oxalic Acid Particlessupporting
confidence: 67%
“…Post-reaction samples were analysed by ion chromatography (IC). R 3 N and NH 3 gas molecules and aminium ions in solution tend to adsorb on surfaces (Dawson et al, 2014;Hansen et al, 2013;Robacker and Bartelt, 1996). To ensure accuracy of the gas ratio, the system was conditioned for several hours to minimise wall losses of either one or both gases prior to the uptake experiment (see Supplement for detailed descriptions).…”
Section: Methodsmentioning
confidence: 99%
“…There is some evidence for this in that stronger correlations were found between polysaccharides and inorganic ions for sub-180 nm than for submicron aerosol, in particular for K+. Previous work has shown that gel-derived aerosol particles contain different cations depending on their morphology, with smaller particles of 10s of nm diameter or their aggregates containing more Na + and K + than Mg 2+ and Ca 2+ (Hamacher-Barth et al, 2016). Larger marine aerosol particles of 0.5 -8.4 µm diameter have also been shown to have polysaccharide-like coatings that contain K + , the only inorganic cation detectable in that study .…”
Section: The Origin Of Polysaccharides In North Atlantic Aerosolsupporting
confidence: 50%
“…Air masses arriving in the Arctic during summer originate from sectors over the oceans with limited man-made activities (Leck and Svensson 2015), and the transport into the Arctic is slower compared to winter conditions (Stohl 2006). Summer conditions are thus much more pristine, and the aerosol shifts to smaller particle sizes (Heintzenberg et al 2015(Heintzenberg et al , 2006 with higher organic content (e.g., Hamacher-Barth et al 2016). Summer pan-Arctic crossings have shown aerosol methanesulfonic acid (MSA; an atmospheric photodegradation product of DMS) concentrations during the phytoplankton growth period to be highest in the Norwegian Sea and lowest over the central Arctic pack ice during the same time (Ye et al 2015), supporting the link between DMS emissions and ice-cover control of air-sea exchange.…”
Section: Field Observations In the Arctic Seasonal Ice Zonementioning
confidence: 99%